Analysis of Nonpoint Source Pollution and Water Environmental Quality Variation Trends in the Nansi Lake Basin from 2002 to 2012 - Weiliang Wang; Tiantian Ju; Wenping Dong; Xiaohui Liu; Chuanxi Yang; Yufan Wang; Lihui Huang; Zongming Ren; Li Qi; Hongyan Wang (Journal of Chemistry)
Based on the data analysis of economic development and the water environmental quality from 2002 to 2012 in the Nansi Lake Basin in China, the correlation between economic development and the water environmental quality was researched. Analysis shows that the GDP of the Nansi Lake Basin had an average annual growth of 7.3% in 2012, and the COD and CODMn had the average annual decrease of 7.69% and 6.79%, respectively, compared to 2002. Basin water environmental quality overall improved, reaching Class III of the “Environmental quality standards for surface water (GB3838-2002).” The pollution of the water environment was analyzed from three aspects: agricultural fertilizers and pesticides, livestock, and aquaculture. Results indicated that the water pollution of the Nansi Lake Basin mainly came from nonpoint source pollution, accounting for more than 80% of the overall pollution. The contributions of both agricultural fertilizers and pesticides account for more than 85% of the overall nonpoint source, followed by livestock and aquaculture. According to the water pollution characteristics of the Nansi Lake Basin, the basin pollution treatment strategy and prevention and treatment system were dissected, to solve the pollution problem of the Nansi Lake Basin.